1996
DOI: 10.1037/0097-7403.22.4.420
|View full text |Cite
|
Sign up to set email alerts
|

Spatial encoding in domestic cats (Felis catus).

Abstract: Four experiments were performed to identify the spatial information that cats used to encode the position of an object they saw move and disappear. In Experiment 1 and 2, several sources of allocentric spatial information were manipulated. Results indicated that the cats used none of these sources and instead relied primarily on their own spatial coordinates (pure egocentric information) to locate the hidden object. In Experiment 3 and 4, pure egocentric information was made unreliable by a detour task. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
2
15
1
Order By: Relevance
“…Our data are to some extent discrepant with those of Fiset and Dore ´(1996). In their study (see Experiment 3), the cats had to recover a target that had been hidden behind one of the three screens displayed in a row in front of the cat.…”
Section: Discussioncontrasting
confidence: 95%
“…Our data are to some extent discrepant with those of Fiset and Dore ´(1996). In their study (see Experiment 3), the cats had to recover a target that had been hidden behind one of the three screens displayed in a row in front of the cat.…”
Section: Discussioncontrasting
confidence: 95%
“…Spotted hyenas have territories that can reach up to 320 km 2 , varying in size with the seasons (Trinkel, Fleischmann, Steindorfer, & Kastberger, 2004), so like wolves and dogs they must be capable of long-range navigation. On the smaller scale, cats are good at locating hidden objects, though relying primarily on egocentric cues (Fiset & Doré, 1996); European badgers have been shown to learn simple spatial discriminations well, using landmarks (Mellgren & Roper, 1986); while American black bears were shown to have comparatively modest spatial learning ability (Zamisch & Vonk, 2012). Perdue, Snyder, Zhihe, Marr, and Maple (2011) found that giant pandas showed sex differences in spatial ability, with males showing greater ability than females, whereas Asian short-clawed otters did not; these results are in accordance with Gaulin and Fitzgerald’s (1986) range size hypothesis, since panda males have larger home ranges than females, but short-clawed otter males do not.…”
Section: The Comparative Projectmentioning
confidence: 99%
“…Relevant data from other species is sparse; there is only scant evidence for a preference for egocentric vs. allocentric cognitive strategies, although what there is mostly suggests an allocentric advantage [Chimpanzee (39); rats (40); cats (41); but see dogs (42) and a gorilla infant (43)]. However, none of these experiments, with infant or animal, used a strictly relational paradigm.…”
Section: Part 2: Phylogenetic Inheritancementioning
confidence: 99%